Magnetic coupling in highly ordered NiO/Fe3O4(110): ultrasharp magnetic interfaces vs. long-range magnetoelastic interactions - Krug, Ingo Peter; Haverkort, Maurits W. (epl, 2008)
We present a laterally resolved X-ray magnetic dichroism study of the magnetic proximity effect in a highly ordered oxide system, i.e. NiO films on Fe 3 O 4 (110). We found that the magnetic interface shows an ultrasharp electronic, magnetic and structural transition from the ferrimagnet to the antiferromagnet. The monolayer which forms the interface reconstructs to NiFe 2 O 4 and exhibits an enhanced Fe and Ni orbital moment, possibly caused by bonding anisotropy or electronic interaction between Fe and Ni cations. The absence of spin-flop coupling for this crystallographic orientation can be explained by a structurally uncompensated interface and additional magnetoelastic effects.